NERDS 3 : the cheerleaders of doom - Buckley, Michael; Beavers, Ethen (New York : Amulet Books, 2011)
When a former member of NERDS turns into a villainous cheerleader, Matilda "Wheezer" Choi and the rest of the NERDS must infiltrate the cheerleader squad and save the world from a machine that wreaks havoc by entering other dimensions.
Accelerated Reader AR
Keywords: Superheroes -- Juvenile fiction; Cheerleading -- Juvenile fiction; Spy stories; Humorous stories; Junior fiction